2014
DOI: 10.1186/1746-6148-10-70
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization and mRNA quantification of osteopontin and Tamm-Horsfall protein in canine renal tissue after potassium oxalate injection

Abstract: BackgroundUrinary macromolecules contribute to promoting or inhibiting crystal retention in renal tissue and stone formation. Osteopontin (OPN) and Tamm-Horsfall protein (THP) are the most important proteins involved in this process. Although these two proteins were discovered a long time ago, their role in setting kidney stone formation has not yet been fully investigated. We conducted a study to explore the role of OPN and THP in canine renal oxalosis. Ten dogs were carefully examined prior to the study. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…In previous studies, an increase in KIM-1 immunoreactivity has been reported semi-quantitatively in the rat kidney tissue after a 1-week exposure to 1% EG [29]. Similar to these studies, EG group showed intense KIM-1 immunostaining compared to the control group but showed a significant reduction in the treatment and pretreatment groups of UD in our study [38]. Many studies have shown that OPN expression is regulated as a protective response to crystal formation and high phosphate levels [39,40,41].…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, an increase in KIM-1 immunoreactivity has been reported semi-quantitatively in the rat kidney tissue after a 1-week exposure to 1% EG [29]. Similar to these studies, EG group showed intense KIM-1 immunostaining compared to the control group but showed a significant reduction in the treatment and pretreatment groups of UD in our study [38]. Many studies have shown that OPN expression is regulated as a protective response to crystal formation and high phosphate levels [39,40,41].…”
Section: Discussionsupporting
confidence: 90%
“…34 The up-regulated corticomedullary OPN mRNA expression level changes in macrodissected cortices and medulla and localization of enhanced OPN immunohistochemistry staining revealed the pathogenesis of chemically-induced mineralization (oxalosis) in naïve adult dog kidneys following exposures to potassium oxalate solutions. Endogenous OPN protein in kidneys is responsible for binding to calcium salts to prevent the formation of calcium oxalate crystals.…”
Section: Discussionmentioning
confidence: 98%
“…The biologic function of the protein is still not fully understood, but it is believed to have roles in water and electrolyte balance in the thick ascending limb of Henle's loop, defense against UTI, prevention against the formation of kidney stones, and in innate immunity of the kidney . Normal urine has high concentrations of THP, and significantly reduced urinary THP concentrations and uTHP/c are seen in dogs and cats with renal disease, including CKD . Furthermore, uTHP/c correlates negatively with plasma creatinine concentration and UPC .…”
Section: Renal Biomarkers: Urinementioning
confidence: 99%